N-(4-(Benzyloxy)-3-methoxybenzyl))adamantane-1-amine (DZH2), a dual CCR5 and CXCR4 inhibitor as a potential agent against triple negative breast cancer - Rostom, Monica M.; El-Zohairy, Mariam A.; Marzouk, Mohamed A.; Berger, Martin R.; Schols, Dominique; Assal, Reem A.; Mandour, Yasmine M.; Adwan, Hassan; Zlotos, Darius P. (Archiv der Pharmazie, 2024)
DZH2, a dual inhibitor of the chemokine receptors CCR5 and CXCR4, was discovered from virtual screening for CCR5 antagonists. In specific Ca2+ chemokine signaling assays, DZH2 displayed low micromolar IC50 values at both chemokine receptors. Its binding to intracellular allosteric binding sites of CCR5 and CXCR4 was confirmed by MD simulations and binding free-energy calculations. DZH2 is superior to the CCR5 antagonist maraviroc in terms of its inhibitory activity on the growth of two breast cancer cell lines. In MCF7 and MDA-MB-231 cells, DZH2 was a >100-fold more potent inhibitor of cell viability compared to maraviroc. DZH2 (6.7 µM) reduced migration of MDA-MB-231 cells to 4% compared to 50% inhibition of migration caused by maraviroc (780 µM). Also, DZH2 was a significantly more potent inhibitor of colony formation in MDA-MB-231 cells than maraviroc. In MCF10 cells, DZH2 caused no alteration in the gene expression with respect to cellular pathways mediating cell death, indicating its selectivity to breast cancer cells.